Sosialisasi Open Defecation Free (ODF) Sebagai Upaya Penguatan Komitmen Masyarakat Menuju Percepatan Desa Odf di Desa Jangur Kabupaten Probolinggo - Ajiputri, Adhiva Calista; Singal, Adeline Nathania Harini; Azizah, Dhiyaa Ummul; Soetikno, Fanny Amanda; Endah Mawarni, Roro Laksmi; Wahyudi, Kalvin Edo (Universitas Gajah Putih, Indonesia, 2023)
Open Defecation Free (ODF) is one of the conditions where a community is no longer practicing open defecation. The aim of the ODF socialization is to create an ODF Jangur Village and reduce the risk of disease due to an unclean and healthy environment. The community service activity carried out by KKNT 55 students at the East Java